Reduced Thalamic and Pontine Connectivity in Kleine–Levin Syndrome - Engström, Maria; Karlsson, Thomas; Landtblom, Anne-Marie (Frontiers in Neurology, 2014)
The Kleine-Levin syndrome is a rare sleep disorder, characterized by exceptionally long sleep episodes. The neuropathology of the syndrome is unknown and treatment is often inadequate. The aim of the study was to improve understanding of the underlying neuropathology, related to cerebral networks, in Kleine-Levin syndrome during sleep episodes. One patient with Kleine-Levin syndrome and congenital nystagmus, was investigated by resting state functional Magnetic Resonance Imaging during both asymptomatic and hypersomnic periods. Fourteen healthy subjects were also investigated as control samples. Functional connectivity was assessed from seed regions of interest in the thalamus and the dorsal pons. Thalamic connectivity was normal in the asymptomatic patient whereas the connectivity between the brain stem, including dorsal pons, and the thalamus was diminished during hypersomnia. These results suggest that the patient’s nystagmus and hypersomnia might have their pathological origin in adjacent dorsal pontine regions. This finding provides additional knowledge of the cerebral networks involved in the neuropathology of this disabling disorder. Furthermore, these findings regarding a rare syndrome have broad implications and results could be of interest to researchers and clinicians in the whole field of sleep medicine.